2003
DOI: 10.1097/00004872-200305000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic subgroup differences in hypertension in Pakistan

Abstract: A threefold difference in prevalence of hypertension exists between people of South Asian descent, which, unlike the urban/rural difference, cannot be accounted for by measured risk factors. Further study would provide valuable etiological and therapeutic clues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
119
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(125 citation statements)
references
References 27 publications
5
119
1
Order By: Relevance
“…The site was chosen as this study was piggybacked to an ongoing study of prevalence of hypertension in this community of individuals belonging to the Pashtun ethnic subgroup (4). A total of 5920 residential structures were numbered and mapped in the study cluster.…”
Section: Sampling Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The site was chosen as this study was piggybacked to an ongoing study of prevalence of hypertension in this community of individuals belonging to the Pashtun ethnic subgroup (4). A total of 5920 residential structures were numbered and mapped in the study cluster.…”
Section: Sampling Detailsmentioning
confidence: 99%
“…Evidence from the Western countries is emerging that migrant populations of South Asian origin have a higher risk for chronic kidney disease (CKD) than the native whites (1)(2)(3). Although no reliable data are available on the incidence and prevalence of CKD in South Asia, the burden of its risk factors, including hypertension and diabetes, in this population is one of the highest in the world (4,5). Therefore, the burden of CKD is expected to be equally high.…”
mentioning
confidence: 99%
“…Two later studies demonstrated that the risk of death and cardiovascular events in people with coronary artery disease are directly related to the degree of renal dysfunction [12,13]. The high prevalence of CKD in the population in Pakistan is not unexpected since the incidence of hypertension and diabetes in Pakistan is one of the highest in the world [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…1 However, data from developing countries on the prevalence of stroke are scarce. 2 Reliable estimates indicate a high prevalence of risk factors for stroke in Pakistan, [3][4][5] but population-based data on the burden of stroke per se in this region are lacking. Evidence from India, while scanty, suggests a high burden of mortality due to stroke, particularly in the younger age group.…”
mentioning
confidence: 99%